On the nature of cancer and why anticancer vaccines don't work - Prehn Richmond T (Cancer Cell International, 2005)
Abstract In this essay I suggest that the major difficulty in producing effective anti-cancer vaccines lies in the fact that most cancers have little immunogenicity because of a basic paucity of tumor-specific antigenicity. The lack of antigenicity, despite extensive genomic instability, could be explained if most tumor mutations occur in silenced genes. A further problem is that an immune reaction against tumor antigens, especially in moderate or low amount, may be stimulatory rather than inhibitory to tumor growth.